Folic Acid‐Modified Mesoporous Silica Nanoparticles for Cellular and Nuclear Targeted Drug Delivery. Issue 2 (28th August 2012) - Porta, Fabiola; Lamers, Gerda E. M.; Morrhayim, Jess; Chatzopoulou, Antonia; Schaaf, Marcel; den Dulk, Hans; Backendorf, Claude; Zink, Jeffrey I.; Kros, Alexander
<x xml:space="preserve">Abstract</x> Folic acid‐modified mesoporous silica nanoparticles are designed for cellular and nuclear targeted drug delivery. Camptothecin is efficiently delivered to human cancer cells resulting in apoptosis without premature leakage. The folic acid moiety is an integral part of a rotaxane structure, which locks the drug molecules in the pores, preventing premature release. Upon folate receptor‐mediated cell uptake, esterases cleave the rotaxane valves and camptothecin is released, resulting in apoptosis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>